Diffuse glioma with FGFR3::TACC3 gene fusion and prominent calcification: A case report - Masaoki Kusunoki; Osamu Togao; Koji Yamashita; Kazufumi Kikuchi; Daisuke Kuga; Yutaka Fujioka; Shun Akamine; Kousei Ishigami (Radiology Case Reports)
Diffuse gliomas with fibroblast growth factor receptor 3 (FGFR3) and transforming acidic coiled-coil containing protein 3 (TACC3) gene fusion represent a distinct molecular subtype of isocitrate dehydrogenase (IDH)-wildtype gliomas characterized by unique histopathological features. Although microcalcifications have frequently been reported in histopathological studies, their prevalence and diagnostic significance on radiological imaging remain unclear. We report a case of a 67-year-old woman who presented with a 1-year history of weakness in the left lower limb. Head CT revealed coarse and irregular calcifications in the deep white matter of the right frontal and parietal lobes. At the same time, MRI demonstrated a diffuse gliomatosis cerebri-like growth pattern with infiltration across the corpus callosum and contrast enhancement in distant areas. Histopathological examination confirmed glioblastoma, IDH-wildtype, and subsequent genetic testing revealed FGFR3::TACC3 fusion and amplification of FGFR3 gene. This case highlights the potential radiological characteristics of diffuse gliomas with FGFR3::TACC3 fusion, particularly the presence of coarse calcifications, that may serve as notable imaging features of this tumor. Further research is required to determine whether calcification is a characteristic of this glioma subtype.